The Relevance of Supreme Court Regulation No. 1 of 2020 in Efforts of State Losses Refund through Restorative Justice - Niko Jaya Kusuma; Firganefi Firganefi; Muhammad Farid (Faculty of Law, Universitas Lampung, 2021)
The government has moved quickly to find a legal breakthrough related to reducing corruption in Indonesia. One of the efforts made by the government is through the Supreme Court to eradicate corruption is the enactment of Supreme Court Regulation No. 1 of 2020 concerning Guidelines for the Criminalization of Articles 2 and 3 of the Law on the Eradication of Corruption Crimes. The consideration is that the imposition of a crime must be carried out with due regard for the certainty and proportionality of punishment to realize justice based on Pancasila and the Republic of Indonesia's 1945 Constitution. The objectives of the Supreme Court Regulation prioritize victim’s losses to be recovered. Moreover, the regulation proportional benefits in imposing penalties on criminal cases is compatible with the Restorative Justice approach. The restorative justice process is expected to be a legal breakthrough in restoring state finances, with dealing with Criminal Corruption Cases focusing on efforts to restore state finances as a whole rather than just prosecuting the perpetrators. Thus, the purpose of this research is to determine how relevant Supreme Court Regulation No. 1 of 2020 are to efforts to recover state losses through restorative justice. This research employs both a normative and an empirical legal approach. Data were gathered through literature reviews and field studies and analyzed qualitatively. The present study confirmed the author's thoughts about the relevancies of Supreme Court Regulation No. 1 of 2020 to recover state losses through restorative justice as Supreme Court Regulation No. 1 of 2020 play a role as a law enforcement's main element as a legal substance.